2008
DOI: 10.3399/bjgp08x342183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2004 GMS contract on practice nurses:

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…For example, several predominantly qualitative studies have explored the impact of the QOF on practice nurses McDonald et al, 2007;McGregor et al, 2008) -yet there is little policy-related discussion of negative impacts on practice nurse workload or morale.…”
Section: The Research Discourse On the Qof So Farmentioning
confidence: 99%
“…For example, several predominantly qualitative studies have explored the impact of the QOF on practice nurses McDonald et al, 2007;McGregor et al, 2008) -yet there is little policy-related discussion of negative impacts on practice nurse workload or morale.…”
Section: The Research Discourse On the Qof So Farmentioning
confidence: 99%
“…quantitative in nature and does not allow for an in-depth exploration of the perceived impact on those conducting the work. While the views and experiences of GP principals and practice nurses have been reported elsewhere, 13,14,23 only two studies have focused on salaried GPs and reported almost diametrically opposing findings. 17 Furthermore, both studies also had limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…12 However, relatively little is known about this group of GPs as much of the post-2004 research has focused on GP principals and practice nurses. [13][14][15] Before 2004, salaried GPs were reported as experiencing lower stress levels than their principal counterparts, 16 and were located in democratic, collaborative practices conducting highly satisfying and varied 'nice work'. 17 By contrast they perceived their GP principals as conducting the 'unrewarding' or 'burdensome' work.…”
Section: Introductionmentioning
confidence: 99%
“…This mirrors the increasingly important role that practice nurses play, particularly in the management of chronic diseases within practices. [35][36][37] It has been suggested that a health check approach is 'simplistic and flawed, in relation to the needs of patients with complex needs' as it does not address the long-term needs of patients. 1 The present study found that Keep Well was developing a system-wide approach, which was attempting to integrate approaches addressing both the health and social determinants of inequalities.…”
Section: Strengths and Limitationsmentioning
confidence: 99%